Application of laparoscopic modified Bacon operation in patients with low rectal cancer and analysis of the changes in anal function: A retrospective single-center study - Lu, Wei; Huang, Shujuan; Ye, Hui; Xiang, Shang; Zeng, Xiangsheng (Frontiers in Oncology, 2023)
Purpose To investigate the value of modified Bacon operation in patients with low rectal cancer. Methods Retrospective analysis of 60 patients treated with laparoscopic surgery for low rectal cancer in the Department of Colorectal and Anal Surgery, Jingzhou Hospital affiliated to Yangtze University, from 2019 to 2022, divided into observation and control groups based on the method of the operation (laparoscopic modified Bacon operation group and laparoscopic Dixon operation with prophylactic ileostomy group). We compared the variations between the two groups. Results The length of the abdominal surgical incision was shorter in the observation group than in the control group(P<0.05). In the observation group, the length of hospital stay after the first operation was shorter(P<0.05), the both operations time and the second intraoperative bleeding were less(P<0.05), the DET score at one week after the first operation and the VAS after both operations were fewer than in the control group(P<0.05), the postoperative rate of ischemic necrosis of the exposed bowel was higher(P<0.05), and the anal function was poorer in the short term after the second operation compared with the control group(P<0.05), but there was no significant difference between the anal function at 6 months after the second operation compared with the control group(P>0.05).12 months after the second operation, the anal function has recovered to the preoperative level in the observation group(P>0.05). Conclusion The laparoscopic modified Bacon operation has smaller abdominal wounds, which reduces postoperative pain; it does not require the use of staplers, which reduces the patient’s financial burden; no postoperative anastomotic leakage occurs, and a more satisfactory anal function can be obtained.